SANITARY AND HYGIENIC CONDITIONS FOR THE ORGANIZATION OF WRITING LESSONS IN PRIMARY SCHOOL - Грітченко, Тетяна (SWorldJournal, 2024)
The article examines sanitary and hygienic conditions for the organization of writing lessons in primary school. The tasks facing the teacher in the context of forming students’ graphic and technical writing skills and preserving their health has been cha